Answer:
the required answer is 125/24.
Answer:
The cost price of one calculator is Rs.750.
The cost price of other calculator is Rs.500.
Step-by-step explanation:
Cost price of 1'st calculator = x
Cost price of 2'nd calculator = 1250-x
He sold one at a profit of 2%.
The selling price of one calculator is
[tex]SP_1=CP(1+\frac{P\%}{100})[/tex]
[tex]SP_1=x(1+\frac{2}{100})[/tex]
[tex]SP_1=x(1+0.02)[/tex]
[tex]SP_1=1.02x[/tex]
He sold other at a loss of 3%.
The selling price of other calculator is
[tex]SP_2=CP(1-\frac{L\%}{100})[/tex]
[tex]SP_2=(1250-x)(1-\frac{3}{100})[/tex]
[tex]SP_2=(1250-x)(1-0.03)[/tex]
[tex]SP_2=(1250-x)(0.97)[/tex]
[tex]SP_2=1212.5-0.97x[/tex]
According to given condition,
[tex]SP_1+SP_2=1250[/tex]
[tex]1.02x+1212.5-0.97x=1250[/tex]
[tex]0.05x=1250-1212.5[/tex]
[tex]0.05x=37.5[/tex]
[tex]x=\frac{37.5}{0.05}[/tex]
[tex]x=750[/tex]
The cost price of one calculator is Rs.750.
The cost price of other calculator is 1250-750=Rs.500.
i am extremely confused, can anyone help?
Answer:
So I did most of you table for you:
First blank:4
Second blank:-4
Third blank:-8
Fourth blank: Left to you: Just plug in 6 into 1/2x^2-5x+4 (I will check)
Fifth blank: Left to you: Just plug in 8 into 1/2x^2-5x+4 (I will check)
The graph is D.
Step-by-step explanation:
So they have a table to fill in and they tell you in the first row what they want you to plug in
So the table is asking us to answer this:
What is h(0),h(2),h(4),h(6), and h(8).
h(0) means to replace x with 0 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2}(0)^2-5(0)+4[/tex]
[tex]0-0+4[/tex]
[tex]0+4[/tex]
[tex]4[/tex]
So the first blank is 4 since h(0)=4.
h(2) means to replace x with 2 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2} (2)^2-5(2)+4[/tex]
[tex]\frac{1}{2} (4)-10+4[/tex]
[tex]2-10+4[/tex]
[tex]-8+4[/tex]
[tex]-4[/tex]
So the second blank is -4 since h(2)=-4.
h(4) means to replace x with 4 in [tex]\frac{1}{2} x^2-5x+4[/tex].
[tex]\frac{1}{2}(4)^2-5(4)+4[/tex]
[tex]\frac{1}{2}(16)-20+4[/tex]
[tex]8-20+4[/tex]
[tex]-12+4[/tex]
[tex]-8[/tex]
So the third blank is -8 since h(4)=-8
Maybe you can try the last 2 blanks in the table part. That is try computing h(6) and h(8). I will check it for you.
Now the points I have so far are (0,4) from the h(0)=4, (2,-4) from the h(2)=-4, and (4,-8) from the h(4)=-8.
I'm looking for a graph that goes through these points (0,4) , (2,-4) , and (4,-8).
By the way the only graphs that are worth looking at is C and D because they are open up. I know my curve for h(x)=1/2x^2-5x+4 should be a parabola open up because 1/2 is positive and 1/2 is the coefficient of x^2.
So Graph C has y-intercept (0,10) not (0,4) so Graph C is not right.
Graph D has y-intercept (0,4). It also goes through (2,-4) and (4,-8).
I don't know if you notice but the x-axis and y-axis are going up by two's in each graph.
Jason deposits $5 into his savings account twice a week for 6 weeks. How much money will he have saved after 6 weeks?
Let s stand for the amount of money saved.
Equation:
How much money did he save?
Show your work.
First person who answers gets to be followed and marked brainliest.
Answer:
60
Step-by-step explanation:
amount of money deposited for one week= $10
no. of weeks= 6
amount= 6*10=60
Jason will have saved $60 after 6 weeks by depositing $5 twice a week.
Jason deposits $5 into his savings account twice a week for 6 weeks. To calculate the total amount saved after 6 weeks, we can set up an equation where s stands for the amount of money saved:
s = number of deposits per week * amount per deposit * number of weeks
Plugging in the values we have:
s = 2 deposits/week * $5/deposit * 6 weeks
s = $60
Therefore, Jason will have saved $60 after 6 weeks.
If y varies directly as x, and y = 2 when x = 4, find y when x = 32.
Step-by-step explanation:
y~x
y=kx
where
y=2,x=4
2=k*4
k=2/4
k=0.5//
find y when x =32
then
y=32*0.5
y=16//
[tex]\bf \qquad \qquad \textit{direct proportional variation} \\\\ \textit{\underline{y} varies directly with \underline{x}}\qquad \qquad y=kx\impliedby \begin{array}{llll} k=constant\ of\\ \qquad variation \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}[/tex]
[tex]\bf \textit{we also know that } \begin{cases} y=2\\ x=4 \end{cases}\implies 2=k(4)\implies \cfrac{2}{4}=k\implies \cfrac{1}{2}=k \\\\\\ therefore\qquad \boxed{y=\cfrac{1}{2}x} \\\\\\ \textit{when x = 32, what's \underline{y}?}\qquad y=\cfrac{1}{2}(32)\implies y=16[/tex]
What is the domain of the function shown in the mapping?
{x | x = -5, -3, 1, 2, 6}
{yly=-9, -6, 0, 2, 4}
{x | x = -9, -6, -5, -3, 0, 1, 2, 4, 6}
{yly = -9, -6, -5, -3, 0, 1, 2, 4, 6}
The domain of the function in the mapping given is: A. {x | x = -5, -3, 1, 2, 6}.
What is the Domain of a Function?The domain of a function includes all the possible values of x (input) in a function.
The corresponding set of y-values (output) is the range of the function.
The set of x-values in the mapping are, -5, -3, 1, 2, 6.
Therefore, the domain of the function in the mapping given is: A. {x | x = -5, -3, 1, 2, 6}.
Learn more about domain of a function on:
https://brainly.com/question/10891721
log5(10x-1)=log5(9x+7)
whats the final answer
Answer:
x = 8
Step-by-step explanation:
log₅ (10x − 1) = log₅ (9x + 7)
10x − 1 = 9x + 7
x = 8
if f(x) =3^x+10 and g(x) =4x -2 find (f+g)(x)
Answer:
[tex](f+g)(x)=3^x+4x+8[/tex]
if [tex]f(x)=3^x+10[/tex] and [tex]g(x)=4x-2[/tex].
Step-by-step explanation:
We are given [tex]f(x)=3^x+10[/tex] and [tex]g(x)=4x-2[/tex].
We are asked to find [tex](f+g)(x)[/tex].
[tex](f+g)(x)[/tex] means [tex]f(x)+g(x)[/tex]
[tex](f+g)(x)=(3^x+10)+(4x-2)[/tex]
You only have one pair of like terms, that is the constants.
[tex](f+g)(x)=3^x+4x+10-2[/tex]
[tex](f+g)(x)=3^x+4x+8[/tex]
Find the image of (1,2) after a
reflection about x = 6 followed by a
reflection about x = 4.
Answer:
(-3,2)
Step-by-step explanation:
When the point P(x,y) is reflected in the line [tex]x=k[/tex], the mapping is
[tex]P(x,y)\to P'(2k-x,y)[/tex].
The image of (1,2) after a reflection about x = 6 is
[tex](1,2)\to (2\times6-1,2)[/tex].
[tex](1,2)\to (12-1,2)[/tex].
[tex](1,2)\to (11,2)[/tex].
When the resulting point is again reflected in the line x=4, we obtain
[tex](11,2)\to (2\times4-11,2)[/tex].
[tex](11,2)\to (8-11,2)[/tex].
[tex](11,2)\to (-3,2)[/tex].
Therefore the image of (1,2) after a
reflection about x = 6 followed by a
reflection about x = 4 is (-3,2)
Measure the angle and classify it as right,acute,or obtuse
Answer:
there is no picture for me to answer on
The table below shows the values of y for different values of x:
x y
0
0
1
5
2
10
3
15
Which equation shows the relationship between x and y?
Answer:
[tex]y=5x[/tex]
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
we have
For x=0, y=0 -----> the line passes through the origin
For x=1, y=5 ----> [tex]k=y/x=5/1=5[/tex]
For x=2, y=10 ----> [tex]k=y/x=10/2=5[/tex]
For x=3, y=15 ----> [tex]k=y/x=15/3=5[/tex]
so
The constant of proportionality is k=5
The table represent a direct variation
The equation is equal to [tex]y=kx[/tex]
substitute the value of k
[tex]y=5x[/tex]
Find the length of the hypotenuse of a right triangle if it’s shorter leg is 12 and longer leg is 16 units
Using the Pythagorean theorem c^2 = a^2 + b^2
Where c is the hypotenuse and a and b are the side lengths.
c^2 = 12^2 + 16^2
c^2 = 144 + 256
c^2 = 400
c = √400
c = 20
The hypotenuse is 20 units.
Answer:
Hypotenuse = 20 units.
Step-by-step explanation:
Using the Pythagoras theorem:
h^2 = 12^2 + 16^2
h^2 = 144 + 256 = 400
h = 20.
Pamela on average serves an ace 44% of the time. If she attempts 25 serves in her next games how many cases would you expect her to have
Answer:
[tex]11\ aces[/tex]
Step-by-step explanation:
we know that
Pamela on average serves an ace 44% of the time
That means ----> Pamela serves 44 aces every 100 serves
Using proportion
Let
x -----> the number of aces
[tex]\frac{44}{100}=\frac{x}{25}\\ \\x=44*25/100\\ \\x= 11\ aces[/tex]
Solve the second equation.
2x - y = 8
First, solve for (-y).
--y =
Answer:
[tex]-y=-2x+8\\y=2x-8[/tex]
Step-by-step explanation:
To solve, first subtract 2x from both sides.
[tex]2x-y=8\\-y=-2x+8[/tex]
You appear to want the solution for -y, so I've included it. Given that you also want the solution for y, divide both sides by -1.
[tex]-y=-2x+8\\y=2x-8[/tex]
Answer:
- y = 8 - 2x
Step-by-step explanation:
2x - y = 8
Subtracting 2x on both sides,
=> 2x - 2x - y = 8 - 2x
=> - y = 8 - 2x
What is the domain and range?
Answer:
ALL REAL NUMBERS
Step-by-step explanation:
Any cubic function is ALWAYS R.
On a horizontal number line, 6 is located to the
of -4. So, -6 is
than-4
On a horizontal number line, -6 is located to the (left) of -4. So, -6 is (less than) 4.
Answer:
On a horizontal number line, -6 is located to the (left) of -4. So, -6 is (less than) 4.
Step-by-step explanation:
Find the simple interest rate needed in order for an investment of $2000 to grow to an account of $5000 in 3 years
[tex]\bf ~~~~~~ \textit{Simple Interest Earned Amount} \\\\ A=P(1+rt)\qquad \begin{cases} A=\textit{accumulated amount}\dotfill & \$5000\\ P=\textit{original amount deposited}\dotfill&\$2000\\ r=rate\to r\%\to \frac{r}{100}\\ t=years\dotfill &3 \end{cases} \\\\\\ 5000=2000(1+r3)\implies \cfrac{5000}{2000}=1+3r\implies \cfrac{5}{2}=1+3r \\\\\\ 5=2+6r\implies 3=6r\implies \cfrac{3}{6}=r\implies 0.5=r\implies \stackrel{\textit{converting to percent}}{0.5\cdot 100\implies 50\%}[/tex]
There was a blizzard. Snow was falling at a rate of 2 ½ inches per hour. If the snow kept accumulating at the same rate, how long would it take for 2 ½ feet of snow to accumulate??
Answer:
12 hours
Step-by-step explanation:
12.5 is 30 inches, at 2.5 inches per an hour you would do 30/2.5 = 12
Evaluate w + (-x) - 2/3, where w = -5/9 and x = 4/3.
Answer:
[tex]\large\boxed{-\dfrac{23}{9}=-2\dfrac{5}{9}}[/tex]
Step-by-step explanation:
[tex]\text{Put}\ w=-\dfrac{5}{9}\ \text{and}\ x=\dfrac{4}{3}\ \text{to the expression}\ w+(-x)-\dfrac{2}{3}:\\\\-\dfrac{5}{9}-\dfrac{4}{3}-\dfrac{2}{3}=-\dfrac{5}{9}-\dfrac{4\cdot3}{3\cdot3}-\dfrac{2\cdot3}{3\cdot3}\\\\=-\dfrac{5}{9}-\dfrac{12}{9}-\dfrac{6}{9}=-\dfrac{23}{9}=-2\dfrac{5}{9}[/tex]
7 1⁄5 – 6 2⁄5 = ?
A. 1 4⁄5
B. 4⁄5
C. 13 3⁄5
D. 1 1⁄5
Answer:
B. 4⁄5
Step-by-step explanation:
7 1⁄5
– 6 2⁄5
-----------------
We need to borrow from the 7 since 1/5 is less than 2/5
7 becomes 6 and the one becomes 5/5
6 5/5+1⁄5
– 6 2⁄5
-----------------
Combining the fraction
6 6⁄5
– 6 2⁄5
-----------------
4/5
what is the volume of the right triangular prism? Round to the nearest tenth
Answer:
V = 306.9 m³Step-by-step explanation:
The formula of a volume of a prism:
[tex]V=BH[/tex]
B - base area
H - height
In the base we have the right triangle.
The formula of an area of a righ triangle
[tex]A=\dfrac{ab}{2}[/tex]
a, b - legs
We have a = 6.2m and b = 11m. Substitute:
[tex]B=\dfrac{(6.2)(11)}{2}=34.1\ m^2[/tex]
The height H = 9 m.
Substitute to the formula of a volume:
[tex]V=(34.1)(9)=306.9\ m^3[/tex]
Using the data: 2, 2, 3, 3, 3, 4, 5, 6, 6, 19
What is Q1 and Q3
Answer:
[tex]Q_1=2[/tex]
[tex]Q_3=6[/tex]
Step-by-step explanation:
Notice that we already have the data sorted from least to greatest.
Now to find Q1 and Q3 we can use the following formulas
For a set of data ordered from least to greatest of the form [tex]X_1, X_2, ..., X_n[/tex]
Where n is the total number of data
[tex]Q_1=X_{\frac{1}{4}(n+1)}[/tex]
In this case [tex]n=10[/tex]
So:
[tex]Q_1=X_{\frac{1}{4}(10+1)}[/tex]
[tex]Q_1=X_{2.75}[/tex]
Round the nearest whole and get:
[tex]Q_1=X_{3}[/tex]
[tex]Q_1=3[/tex]
For Q3 we have:
[tex]Q_3=X_{\frac{3}{4}(n+1)}[/tex]
[tex]Q_3=X_{\frac{3}{4}(10+1)}[/tex]
[tex]Q_3=X_{8.25}[/tex]
Round the nearest whole and get:
[tex]Q_3=X_{8}[/tex]
[tex]Q_3=6[/tex]
Answer:
Q1: 2.5
Q3: 6
Step-by-step explanation:
The median area is 3 and 4.
The lower quartile is 3+2=5 5/2 2.5
The upper quartile is 6+6= 12 12/2 6
Subtract (3x^2 + 2x+4) - (x^2 +2x+1) =
Answer:
2x^2+3
Step-by-step explanation:
(3x^2 + 2x+4) - (x^2 +2x+1)
I'm going to rewrite this using distributive propery and without parenthesis:
3x^2 + 2x + 4 - x^2 - 2x - 1
Now I'm going to pair up any like terms by use of the commutative property.
3x^2 - x^2 + 2x - 2x + 4 - 1
Now simplify:
2x^2 + 0 +3
2x^2+3
Answer:
The final value of subtraction is 2x² + 3
Step-by-step explanation:
It is given that (3x² + 2x + 4) - ( x² + 2x + 1)
To find the value of subtraction
(3x² + 2x + 4) - ( x² + 2x + 1) = (3x² + 2x + 4 - x² - 2x - 1)
= 3x² - x² + 2x - 2x + 4 - 1
= 2x² + 0 +3
= 2x² + 3
Therefore the final value of subtraction is 2x² + 3
What is the completely factored form of the expression 16x2 + 8x + 32?
4(4x2 + 2x + 8)
4(12x2 + 4x + 28)
8(2x2 + x + 4)
8x(8x2 + x + 24)
Answer:
[tex]8(2x^2 + x + 4)[/tex]
Step-by-step explanation:
Given:
[tex]16x^2+8x+32[/tex]We'd factor out 8:
[tex]8(2x^2 + x + 4)[/tex]
Our answer would be [tex]8(2x^2 + x + 4)[/tex]
The completely factored form of the expression 16x2 + 8x + 32 is 8(2x2 + x + 4), after factoring out the greatest common factor, 8.
The question asks for the completely factored form of the expression 16x2 + 8x + 32. To factor this expression completely, we look for a common factor in all the terms. Observing the coefficients (16, 8, and 32), we recognize that 8 is the greatest common factor (GCF). Factoring out the GCF, we get:
8(2x2 + x + 4).
This expression cannot be factored further since the quadratic inside the parentheses does not factor neatly over the integers. Thus, the completely factored form of 16x2 + 8x + 32 is 8(2x2 + x + 4).
What is the solution to 2h +8 > 3h - 6
Answer:
h < 14
Step-by-step explanation:
2h +8 > 3h - 6
2h - 3h > - 6 - 8
-h > -14 (multiply both sides by -1; remember to flip the inequality sign!)
h < 14
Which expression is the factored form of −1.5w+7.5 ?
a) 1.5(5+w)
b) 1.5(w−5)
c) −1.5(w−5)
d) −1.5(w+5)
Answer:
c.
Step-by-step explanation:
the most that can be factored out is -1.5,
-1.5 * w = -1.5w
-1.5 * -5 = 7.5
-1.5w + 7.5, so it's
-1.5(w-5)
What is the image of (9,-5) after a dilation with the scale factor of 2.5?
gary had $230. he spent 45% of the money on a wallet. how much money did he have left?
Answer: $126.50
$230×.45= $103.5
$230-$103.5=126.50
Answer:
126.50
Step-by-step explanation:
If he spent 45% of the money, he still has 100% -45% = 55%
He will still he have 55% of his money
230* 55%
Changing to decimal form
230*.55
126.50
the weight of a bucket is 33/2 kg. if 1/4 of the bucket contains water weighing 21/4 kg , determine the weight of empty bucket
Answer:
15.733kg
Step-by-step explanation:
33.2 - 21.4 = 11.8
3/4 of the bucket empty is 11.8kg.
11.8 divided by 3 is 3.933. 3.933 x 4 is 15.733
Is Erik's statement correct? Why or why not?
Yes, the solids are both cones and appear to have
the same volumes.
Yes, the area of the bases and the heights of the
cones are the same, so the volumes are equal.
O No, the heights of the cones are not the same, so
Cavalieri's principle does not apply.
Answer:
Step-by-step explanation:
No, the heights of the cones are not the same, so Cavalieri’s principle does not apply.
Can someone solve these?
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept
[tex]61)\ m=3,\ b=-2\\\\\boxed{y=3x-2}\\\\62)\ m=\dfrac{4}{5},\ b=4\\\\\boxed{y=\dfrac{4}{5}x+4}\\\\63)\ m=-\dfrac{7}{4},\ b=-3\\\\\boxed{y=-\dfrac{7}{4}x-3}\\\\64)\ m=-\dfrac{3}{4},\ b=-2\\\\\boxed{y=-\dfrac{3}{4}x-2}[/tex]
Simplify: 3x – 5 + 23x – 9
Simple form of equation 3x – 5 + 23x – 9 = 26x-14
Further ExplanationLinear Equation in One Variable is an equation that has a variable and the exponent number is one.
Can be stated in the form:
[tex] \large {\boxed {\bold {ax = b}} [/tex]
or
ax + b = c, where a, b, and c are constants, x is a variable
Whereas Linear Equation in two Variable is a linear equation that has 2 variables and the exponent is one
Can be stated in the form:
[tex] \large {\boxed {\bold {ax + bx = c}}} [/tex]
x, y = variable
There are several ways to solve an equation
• Add / Subtract / divide / multiply the same value on both sides
• Combine like terms
• Factoring
• Expanding
Like terms are terms whose variables and their exponents are the same.
You can combine and add terms
The algebraic form of 3x - 5 + 23x - 9 is a Linear Equation in One Variable, can be simplified:
• 1. Combine like terms
(3x + 23x) + (-5 - 9)
• 2. Add like terms:
26x -14
Learn morean algebraic expression
brainly.com/question/20988
brainly.com/question/2285423
brainly.com/question/2241589
[tex]\(3x - 5 + 23x - 9\)[/tex] simplifies to [tex]\(26x - 14\).[/tex]
To simplify the expression [tex]\(3x - 5 + 23x - 9\)[/tex], we can combine like terms
[tex]\[3x - 5 + 23x - 9 = (3x + 23x) + (-5 - 9)\][/tex]
[tex]\[= 26x - 14\][/tex]